Produksi Poli-β-hidroksibutirat (PHB) Menggunakan Bakteri Bulkhoderia cepacia - Sri Wahyu Murni; Gunarto Gunarto (Eksergi, 2008)
Plastics have important roles nowadays. However, its non-biodegradable property potentially makes a great problem because of the accumulation of its waste. Therefore, many researches about biodegradable plastics have been developed. Poly-β-hydroxybutyrate (PHB) is an alternative material to produce biodegradable plastics. The objectives of this research are to study the production of PHB by using Bulkhoderia cepacia bacteria and soluble starch substrate and determine the kinetics parameters including maximum specific growth rate (μmaks), saturation constant (Ks), and yield ratio of product-to-bacterial cell (YP/X). Fermentation was conducted at room temperature by using Ramsay medium with soluble starch at certain concentrations. The starter of Bulkhoderia cepacia incubated for 24 hours was inoculated as many as 10% by volume. The PHB product and dry cell weight were analyzed at certain several time intervals. This experiment was repeated at variation of phosphate concentrations.This research showed that the optimum cell growth and PHB production was obtained at soluble starch concentration of 8 g/100 ml and growth period of 72 hours. At this condition, the results were the dry cell weight of 7.5 mg/ml and PHB concentration of 0.0095 mg/ml. The values of kinetics parameters were μ maks of 0.01292 g/ml. h, Ks of 0.2854 g/ 100ml, YP/X of 0.00143. The accumulation of PHB was optimum at limited phosphate concentration. It could be also concluded that Bulkhoderia cepacia was a non-effective bacteria to produce PHB.